Scrolling the Line: Navigating the Impact of Social Networking Sites Usage on Corporate Employees’ Work Productivity - Salleh, Sazimah Mohamed; Rahim, Ramita Abdul; Sari, Nor Afni Md; Zainal, Noor Zalina; Mohammed, Adilah Afiqah; Shamsudin, Siti Nazeera (Advances in Social Sciences Research Journal, 2024)
In the era of technological advancement, physical activities have taken a backseat as individuals increasingly find themselves immersed in the digital realm, particularly with the pervasive use of smartphones. Corporate employees, in particular, conduct their work online, often multitasking with leisure activities on Social Networking Sites (SNS). This research delves into the experiences of corporate employees in relation to SNS use and explores the consequences of excessive social media engagement during work hours. The study, based on data collected from 130 respondents across various organizations, reveals that SNS usage significantly surpasses knowledge sharing as the primary factor influencing both SNS use and work productivity. Through correlation analysis using SPSS Version 27, this research offers valuable insights into the intricate dynamics between SNS use, work engagement, and productivity. The findings are poised to make a substantial impact on organizational strategies, providing essential knowledge for SNS strategists and policymakers to harness the potential benefits of social media usage in the workplace.